The function of Sphingosine-1-phosphate receptor 2 (S1PR2) in maintaining intestinal barrier and inducing ulcerative colitis. Issue 5 (2nd May 2022) - Chen, Tanzhou; Gu, Kaier; Lin, Ruoyang; Liu, Yang; Shan, Yunfeng
ABSTRACT: Sphingosine-1-phosphate receptor 2 (S1PR2) was highly expressed in intestinal epithelial cells (IECs) and facilitated the proliferation of IECs. However, the specific function of S1PR2 in intestinal diseases, such as ulcerative colitis (UC), remains unclear. Accordingly, the current study set out to investigate the function of S1PR2 in maintaining intestinal barrier and inducing UC. S1PR2-overexpressed and knockdown Caco-2 cells were established to explore the function of S1PR2 on the permeability of IECs barrier. The UC-like mouse model in which UC is induced by dextran sulfate sodium (DSS) was established and utilized to investigate the role for S1PR2. The results showed that S1PR2 functioned as a maintainer of IECs permeability and a pathogenic factor for UC. A series of in vitro and in vivo experiments were conducted, and it was found that S1PR2 played an important role in intestinal epithelial cell proliferation and maintenance of intestinal epithelial cell barrier, possibly by the regulation on the expression level of SphK2, HDAC1, HDAC2, and ERK1/2 signaling pathway. The expression of S1PR2 was upregulated in UC mice and the colonic pathological damage in UC mice could be alleviated by the inhibition of S1PR2. Collectively, these results suggest that S1PR2 functions as a maintainer of IECs permeability and a pathogenic factor for UC. The research suggests S1PR2 may be an effective target for developing therapeutic strategies against UC. Abbreviations: S1PR2, Sphingosine-1-phosphate receptor 2; UC, ulcerative colitis; IECs, intestinal epithelial cells; DSS, dextran sulfate sodium; IBD, inflammation bowel disease; CD, Crohn's disease; S1P, sphingosin-1-phosphate; SphK, sphingosine kinase; HIECs, human IECs; siRNA, small interfering RNA; CCK-8, cell counting kit-8; TEER, transepithelial electrical resistance; TEM, transmission electron microscope; RT-PCR, real-time reverse transcriptase polymerase-chain reaction; ELISA, enzyme-linked immunosorbent assay; HE, hematoxylin and eosin. GRAPHICAL ABSTRACT: uf0001